3D-phosphorus doped mesoporous graphitic carbon nitride based immunosensor for swine flu detection. (7th October 2022) - Nirbhaya, Vishakha; Kumar, Yogesh; Chandra, Ramesh; Kumar, Suveen
Abstract : Illustrative representation of the immunosensing platform and its electrochemical response for the detection of swine flu. Abstract : The present study concerns the exposure and transmission of virus-borne disease and the protein serum amyloid A (SAA), which may act as a hallmark biomarker for swine flu (SF) detection. The concentration of SAA protein in the serum of a normal subject is 12.2 ± 15.0 μg mL −1, which increases to 49.4 ± 14.1 μg mL −1 in a SF-infected patient. In the present work, we have developed an immunosensor platform for SF detection. For this, three dimensional (3D)-phosphorus doped porous graphitic carbon nitride (P-g-C3 N4 ) was synthesized via a chemical process and functionalized with serine (Ser) molecules. The functionalized nanomaterial (Ser/P-g-C3 N4 ) was electrophoretically deposited onto an indium tin oxide (ITO) coated glass electrode. The prepared Ser/P-g-C3 N4 /ITO electrode was biofunctionalized via covalent immobilization of anti-SAA antibodies and then incubated with bovine serum albumin molecules for non-specific site blocking. Structural, morphological, chemical, and surface analysis studies of the synthesized nanomaterial and fabricated electrodes were carried out using X-ray diffraction, Brunauer–Emmett–Teller theory, Fourier transform infrared spectroscopy, contact angle, scanning electron microscopy, field emission scanning electron microscopy, and transmission electron microscopy techniques. Electrochemical characterization and analytical evaluation/studies of the fabricated electrodes were performed using cyclic voltammetry, differential pulse voltammetry, and electrochemical impedance spectroscopy techniques. The fabricated immunosensor, i.e., BSA/anti-SAA/Ser/P-g-C3 N4 /ITO, is capable of providing a sensitive and specific response to SAA protein in an analytical solution over the concentration range of 10 ng mL −1 to 100 μg mL −1, with a lower detection limit of 10 ng mL −1, excellent sensitivity of 23.9 μA log (mL ng −1 ) cm −2, and quick analysis time (10 min). Comprehensively, the fabricated immunosensor was also used to analyze SAA protein in spiked serum samples, which resulted in a good correlation with the electrochemical response observed in standard SAA protein samples in analytical solution.